Analysis-oriented model for partially FRP-and-steel-confined circular RC columns under compression. (1st February 2023) - Shayanfar, Javad; Barros, Joaquim A.O.; Rezazadeh, Mohammadali
Highlights: A new methodology for the determination of FRP-steel dual confinement is introduced. A new dilation model for partial confinement is proposed. Consideration of non-homogenous distribution of concrete expansion enhances the model's predictive performance. A new failure surface function is suggested for calculating FRP-steel dual confinement-induced enhancements. Proposed model could predict accurately the influence of partial confinement on axial and dilation behavior of RC columns. Abstract: Even though analysis-oriented models exist to simulate the axial and dilation behavior of reinforced concrete (RC) columns strengthened with fiber-reinforced-polymer (FRP) full confinement arrangements, a reliable model developed/calibrated for FRP partially imposed confinements is not yet available, identified as a research gap. Therefore, this paper is dedicated to the development of a new analysis-oriented model generalized for fully and partially confined RC columns under compression. In addition to vertical arching action phenomenon, the influence of the concrete expansion distribution along the column height on confining stress is considered in the establishment of the combined confinement from FRP strips and steel transverse reinforcements. A new unified dilation model is proposed, where the substantial effect of additional axial deformations induced by damage evolution in unwrapped zones is formulated by considering available experimental results. This model is coupled with an axial stress-strain formulation that includes a new failure surface function for simulating the dual confinement-induced enhancements, which are strongly dependent on the confinement stiffness. The developed model considers the influence of partially imposed confinement strategy on the axial and dilation behavior of RC columns, whose validation is demonstrated by simulating several experimental tests. Lastly, a parametric study is performed to evidence the dependence of FRP-steel confinement-induced enhancements on steel hoop and FRP spacing, and on the concrete compressive strength.